Downloading contracts from register of contracts - Kříha, Jakub; Bruckner, Tomáš, 1974-; Šperková, Lucie; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
The topic of this bachelor's thesis is development of a script for downloading and filtering entries from public registry of contracts of Ministry of the interior of the Czech Republic. This thesis is part of a project to create price-list of ICT work for state institutions. The goals of this thesis include introduction of the price-list project, draft of download script's functionality, description of follow-up data processing, trying out two different programming languages of the script and final deployment of chosen script in production. My thesis contributes to creation of price-list of ICT work, which is important for evaluating offers in open tenders.
Vedoucí práce: Tomáš Bruckner
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses